Selecting the Best Strategy for Industry 4.0 Applications with a Case Study - Erdogan, Melike; Ozkan, Betul; Karasan, Ali; Kaya, Ihsan (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
In this paper, we try to find the best strategy for Industry 4.0 implementation. For this aim, we determine the aggregated strategies for applying this concept and criteria that are used to select the best strategy. With the criteria set out in this context, basic strategies should be applied as a priority, considering for example human resources, work organization and design, information systems, and effective use of resources, and the development of new business models and standardization are specified. Since this selection is a process in which many different measures need to be considered, multi-criteria decision-making (MCDM) methods based on AHP-VIKOR methodologies have been applied to find the best strategy. Fuzzy set theory was beneficial for coping with uncertainties in the selection process.
Keywords: Fuzzy sets; Industry 4.0; Multi-criteria decision making; Strategy selection; MULTICRITERIA DECISION-MAKING; FUZZY; VIKOR; TOPSIS; Engineering